Options in Repositioning the Asymmetric Brow from Paralysis and Trauma - Lee, Thomas S.; Wang, Lexie; Han, Reintine; Mourad, Moustafa; Ducic, Yadranko (Facial Plastic Surgery, 2017)
Brow asymmetry is a relatively common occurrence, especially in the facial plastic surgeon's office. In this article, the authors review causes of brow asymmetry, pertinent anatomy, and a litany of treatment options including nonsurgical and surgical approaches. They offer an algorithm that summarizes the various techniques for management with the goal of tailoring treatment tactics to the individual patient's needs.
Keywords: brow ptosis; brow lift; brow asymmetry; facial nerve paralysis